The Students Interest Related with Teacher Strategy: English - Asyaari Asyaari (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
Arousing interest in learning in students must be a strategy applied by the teacher, in choosing a strategy a teacher must be able to adapt to the needs of his students. This strategy helps students to stay concentrated and focused on the material so that it really help student in learning in the class. The research objectives to be achieved in this study are .To find out the strategies applied by English teachers to students' interest. To find out what factors influence student interest in learning. The qualitative method uses a phenomenological approach. While the type of research used in qualitative. Qualitative research is research that intends to understand the phenomena of what happens and is experienced by research subjects such as behaviour, perceptions of motivation and actions and others by means of descriptions in the form of words and language.